EFL LEARNERS’ LEARNING STYLE PREFERENCES IN RELATION TO THEIR ENGLISH PROFICIENCY - Manan, Siti Saleha; Suhartini, Lelly; Muhsin, Muhammad Khusnun (Universitas Halu Oleo, 2019)
The aim of this study was to find out students’ learning style preference and its correlation with their English Proficiency. The research questions were as follows (1) what are the most preferred learning styles of EFL Learner at English Department? (2) Is there any significant correlation between students’ learning style preferences and their English Proficiency? The study used Correlation design. The number of sample in this study was 35 students from English department of Halu Oleo University in the academic year who had followed TOEFL test. The data were collected using questionnaire which adopted Perceptual Learning-Style Preference Questionnaire (PLSPQ), developed by John Reid (1987) consisting of 30 statements and student’s TOEFL score. The data of this study were analyzed through descriptive statistic and Linear Regression Analysis. The results showed that (1) major learning style were tactile learning style and kinesthetic learning style (2) The coefficient correlation was 0.070 which was greater than 0.05 (level of significance). It means that there was no correlation between students’ learning style and their English proficiency.Keywords: Student’s Learning Style, English Proficiency.